STUDENT WORKSHEETS OF PBL AND PROBING PROMPTING TECHNIQUE ON CRITICAL THINKING SKILLS - Pereira, Vitoria Venisia; Samsudin, Achmad; Utama, Judhistira Aria (Journal of Teaching and Learning Physics, 2023)
In the 21st century Critical thinking skills are considered important. One of the media that can use to practice critical thinking skills is student worksheets. This study aims to discuss the design of student worksheets based on problem-based learning models assisted by probing-prompting techniques to improve critical thinking skills in physics learning. The method used in this study is a literature study as an initial stage of the development design. The results of the literacy study show that student worksheets are a companion material in the learning process that will make teacher and student interaction more effective, the material becomes easier to understand, and students are more active in critical and creative thinking so that thinking ability can be achieved. Therefore, it is advisable for subsequent researchers to try to develop again the worksheets of the students in this study and test the results of the development in physics classes.